Me HUBUNGAN ANTARA KONFORMITAS TEMAN SEBAYA DAN POLA ASUH OTORITER DENGAN KECANDUAN GAME ONLINE PADA SISWA SMK KOTA BENGKULU: Judul, Abstrak, Pendahuluan, Metode Penelitian, Hasil dan Pembahasan, Kesimpulan dan Saran, Daftar Pustaka - Fitriza Hazanah; Yessy Elita; Anni Suprapti (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2024)
The purpose of this research was to describe the relationship between peer conformity and authoritarian parenting with online game addiction among Vocational School students in Bengkulu City. The research population amounted to 219 and the research sample amounted to 140, which was obtained from a random sampling technique. This research design used was a quantitative descriptive method using regression analysis. The data collection tool used was a questionnaire. The results obtained in this research indicate a positive and significant relationship between peer conformity and online game addiction, this means that the higher the peer conformity, the higher the online game addiction, conversely the lower the perception of peer conformity, the lower the online game addiction in students with an effective contribution of 24.6%. There was a positive and significant relationship between authoritarian parenting and online game addiction, it means that the higher the perception of authoritarian parenting, the higher the online game addiction and conversely the lower the perception of authoritarian parenting, the lower the online game addiction with an effective contribution of 9.1%. Keywords: Peer conformity, authoritarian parenting, online game addiction